When Risk-Taking Meets ESG: Implications for Firm Performance in Indonesia - Hesniati; Stefani, Christine; Budiman, Johny (Manunggal Halim Jaya, 2025)
This study explores the relationship between firm risk-taking and financial performance, with a particular focus on the moderating role of Environmental, Social, and Governance (ESG) practices. Using panel data from 86 firms listed on the Indonesia Stock Exchange over the 2018–2023 period, Ordinary Least Squares (OLS) regression with year fixed effects was employed. The results show that risk-taking has a positive and significant effect on firm performance, supporting the risk–return trade-off perspective. However, the interaction term reveals a negative moderation, meaning that ESG weakens the relationship between risk-taking and firm performance. This suggests that firms with stronger ESG commitments adopt more cautious strategies, which may reduce short-term financial gains but reinforce long-term stability and stakeholder trust. The findings contribute to the literature by clarifying the dual role of ESG as both a performance enhancer and a risk-control mechanism in emerging markets. Managers should integrate ESG principles into their strategic risk management frameworks to ensure that risk-taking decisions are aligned with sustainability objectives. Future studies should adopt broader risk-taking measures (R&D investment or leverage), extend the scope to cross-country settings, and integrate qualitative approaches for deeper insights.